Desulphurization of Model Oil using Immobilized [BMIM]FeCl4 onto Polysulfone (PSF) - MOHAMAD IBRAHIM BIN MOHD ZOLKEPLI, MOHAMAD IBRAHIM (Universiti Teknologi Petronas, 2010)
Final Dissertation of the experiment “Desulphurization of Model Oil using Immobilized [BMIM]FeCl4 onto Polysulfone (PSF)” is the requirement of complementation of Final Year Project 2. Desulphurization has become one the important criteria that need to be concentrated especially in oil industries. Other than the conventional Hydrodesulphurization, many methods and alternatives have been discovered and yet to be discovered on order to cater the advance technology of Chemical Engineering, as well as the quality of the existing crude oil throughout the world. One of the major methods is desulphurization using ionic liquids. Ionic liquid is a new technology that can help to improve the quality of desulphurization due to its nature and function. [BMIM}FeCl4 has been found out that it is the most suitable ionic liquid to desulphurize model oil. However, a limitation occurs as the ionic liquid exists in liquid form which later will cause a problem in doing the Liquid-Liquid Extraction. Thus, a new method is required to overcome this problem, which is the immobilization technique, Spraying Suspension Dispersion (SSD). SSD can immobilize any ionic liquid onto a solid structure, such as [BMIM]FeCl4 onto Polysulfone (PSF). It works by dissolving the [BMIM]FeCl4 together with PSF using dichloromethane and later they are sprayed into water solution. The water will wash away dichloromethane and as a result, droplets of PSF with [BMIM]FeCl4 onto it are produced. These droplets will solidify and become a solid compound. The results from characterization has proven that [BMIM]FeCl4 has been successfully hooked onto PSF. The desulphurization results also have shown that the immobilized [BMIM]FeCl4 can still remove sulphur from model oil. Thus, this is a new method of desulphurization that engineers can go into and study into details.